2016
DOI: 10.1136/bmjquality.u209900.w4090
|View full text |Cite
|
Sign up to set email alerts
|

Improving residents' handovers through just-in-time training for structured communication

Abstract: In a recent quality assurance project we learned that nearly half of the handovers we examined were characterized as unsatisfactory by our residents, who provided examples in which their anxiety had been piqued and patient care had been affected. These reports substantiated a growing body of literature on the relationship between the quality of handover and the quality of patient care, so we sought to improve the quality and consistency of the in-hosptial handovers undertaken by our internal medicine residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Some of our training residents thought the whole endorsement process does not affect the patient care in the PICU, thinking that this relates more to the PICU senior staff themselves rather than relating to the trainees. This misconception highlights that training residents need more education on how proper endorsement affects the quality of patient care and safety (43). Having all PICU team members share the handover information about a patient’s current situation, assessments, and care recommendations could prevent near misses and adverse events (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of our training residents thought the whole endorsement process does not affect the patient care in the PICU, thinking that this relates more to the PICU senior staff themselves rather than relating to the trainees. This misconception highlights that training residents need more education on how proper endorsement affects the quality of patient care and safety (43). Having all PICU team members share the handover information about a patient’s current situation, assessments, and care recommendations could prevent near misses and adverse events (43).…”
Section: Discussionmentioning
confidence: 99%
“…This misconception highlights that training residents need more education on how proper endorsement affects the quality of patient care and safety (43). Having all PICU team members share the handover information about a patient’s current situation, assessments, and care recommendations could prevent near misses and adverse events (43). Unfortunately, such vital information does not always pass flawlessly from the previous to the subsequent healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that omission or distortion of important clinical information occurs during transition of care 5,6,9,11. This study sought to address issues of miscommunication during sign-out through utilization of a standardized checklist.…”
Section: Discussionmentioning
confidence: 99%
“…If done poorly, sign-outs can have deleterious clinical impact. The Institute of Medicine attributes a substantial proportion of preventable adverse events to communication errors during sign-out 5. These errors are among the root causes of nearly two thirds of potentially significant, preventable adverse clinical outcomes in hospitals 6,7…”
Section: Introductionmentioning
confidence: 99%
“…The Institute of Medicine atributes a substantial proportion of preventable adverse events to communication errors during handover [11]. The Agency for Healthcare Research and Quality identiies handof communication miscues as implicated in surgical errors [12] and as a consequential cause of malpractice claims.…”
Section: Insuicient Handofs Induce Complicationsmentioning
confidence: 99%